Sustainable Economic Development: the Ethical Aspects of Alternative Models of the Society Development - Čiegis, Remigijus (Ekonomika, 2001)
People are going to the next millenium, in which must be formed new attitudes to the environment, scientific and technological progress, integration of different cultures and traditions and economical development. In the last century used the concept of the economical development today is impossible to use without changes. If we are taking in the account externalities and negative consequences of economical actions, we must again to think about theoretical background of economical life. In the reality we are needing to have a new global economical theory, which can help us to change the old economical policy.But before such theory will be created, the existence of alternative models is only one possibility not to go to the bankruptcy of the society. So, we are needing to have a new, alternative ideas about development of the society. (We can say, that alternative models are reaction of the economical thinking to the complex problems of our days - ecological, technological, social).The concept of the sustainable development, without which is impossible to imagine discussions about environment and development, is real alternative in the economical theory to the neoclassical growth theory, speaking about economical growth which means quantitative material growth of the economy. The idea of sustainable development can help us to stop the destruction of natural resources and to put the economy to the qualitative growth (development). In the reality the sustainability is a normative ethical principle of the social development, which speaks not about things, how they are, but about things, how they must be. The sustainability is not a technical problem, which we must to solve, but “the vision of the future, which helps us to concentrate our attention to the values and ethical and moral principles”. So, sustainable economical solutions can be found only if will be fundamental changes in the human value attitudes, and will be created a new view to the nature.More and more attention for the ethical dimension of the sustainable development are given in the scientific economical literature. In this paper the authors analyses questions, which are related to the sustainable economical development and emphasize ethical aspects of this path of economy. Ethical aspects are very important, because now the humanity is faced with the principle problem - to have or not to have the future. Today if we want to make economical decisions, it is not enough to have sufficient economical information and narrow criterion of economical efficiency. We are needing to have other criterions - ecological, ethical - which are very important for the sustainable development of theworld. Ecological-ethical imperative shows the limit, beyond which the sustainable life becomes impossible.The goal of the paper was to analyse alternative ideas of the economical development, to find its the historical. social and cultural roots and relations, to give the alternative attitude to social development. Ethical limits for economical activities in the sustainable development model are analysed too.